Program Literasi di SDN 112 Pekanbaru, SDN 161 Pekanbaru, SDN 018 Kubang Raya dan SDN 028 Rimbo Panjang - Angguni Yasmin; Rahmi Murniyati; Resti Andini Dwi Hendriatmi; Syahira Nabila; Febrina Dafit (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The problem in this study is related to the implementation of literacy in elementary schools (SD). This study uses a literature study from previous research observation reports. Data tracking is done by conducting searches during observations in elementary schools. From the results of the search, it was found that several literacy practices were implemented in elementary schools and regarding literacy that had not been implemented in elementary schools. The obstacles encountered in implementing some of the non-existent literacy are demanding the abilities of students and teachers, students who have not been able to think critically and teachers who do not know how to apply it properly and correctly.